CMMI assessments : motivating positive change - Bush, Marilyn (SEI series in software engineering., 2005)
Use Assessments to Drive Process Improvements in Software, Systems, Human Resources, and Beyond Pioneered by the world's leading innovators in software engineering, assessments have evolved into a remarkably powerful tool for process improvement in areas ranging from systems to services, hardware to human resources. Unlike audits, assessments are conducted from the inside. When handled correctly, assessments can help transform technical and managerial culture, dramatically improving both quality and profitability. In CMMI Assessments: Motivating Positive Change , two of the field's most respected leaders show exactly how to use them for maximum business advantage. Writing for executives, managers, technical professionals, and assessors themselves, Marilyn Bush and Donna Dunaway illuminate every phase of the assessment process-from planning through post-assessment follow-up. The authors begin with an expert overview of what assessments entail, when they make sense, how to set achievable goals for them, and how to lead them to success. Next, they "drill down" into each stage of the process, presenting step-by-step instructions and defining the roles and responsibilities of every participant. Coverage includes creating and training assessment teams; identifying assessment products; consolidating interview data and other onsite activities; presenting results; and using those results productively. Drawing on their unsurpassed experience leading assessments and mentoring assessors, they offer deep insights into the real-world challenges and obstacles you'll face-and proven solutions. They also present an extended case study showing how a real software development organization drove continuous improvement through four years of iterative assessments-moving from CMM Level 2 to elite Level 5 status, and driving dramatic business benefits along the way. © Copyright Pearson Education. All rights reserved.